Investigating factors affecting adoption of eCRM in the Australian service industry - Lin, Chad; Jalleh, Geoffrey (IGI Global, 2015)
© 2015 by IGI Global. All rights reserved. In order to grow and survive in a highly competitive market like the service industry, Electronic Customer Relationship Management (eCRM) has become a popular tool for Australian service organizations to attract, manage, and enhance customer relationships. However, due to increased competition and decreased product/services marketing cycle time, managing and building customer relationships have become a challenge for most service organizations. Ineffective eCRM adoption process can result in financial losses for the organizations. Hence, case studies are conducted to identify and examine potential IT costs and risk factors involved in the adoption of eCRM projects. The findings in the chapter provide senior executives with a more realistic insight into dealing with issues and challenges arising from the adoption of eCRM.